2022
DOI: 10.1155/2022/7387409
|View full text |Cite|
|
Sign up to set email alerts
|

Surface State Treatment of Carbon Dots Using Sulphur Dioxide Isotherm

Abstract: Low toxicity carbon dots are combating the disadvantages of quantum dots. The carbon dots find their applications in many fields due to their versatile nature. Four different types of carbon dots are present, according to the way of manufacturing and application the type is chosen. The water-soluble characteristics of carbon dots help them be involved in biomedicine applications. The optical properties of the carbon dots find applications as drug delivery, biosensors, LED, etc. The properties like fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the MgO/biochar nanocomposites specimens, MB sorption was initially enhanced and then diminished with MgO and concluded that there may be a perfect balance among MgO and biochar for removing contaminants [28]. Ag/MgO/biochar at 1 : 1 ratio of composites had the best P removal effectiveness in this work, combined with acceptable large efficiency for MB sorption [29].…”
Section: Resultsmentioning
confidence: 95%
“…In the MgO/biochar nanocomposites specimens, MB sorption was initially enhanced and then diminished with MgO and concluded that there may be a perfect balance among MgO and biochar for removing contaminants [28]. Ag/MgO/biochar at 1 : 1 ratio of composites had the best P removal effectiveness in this work, combined with acceptable large efficiency for MB sorption [29].…”
Section: Resultsmentioning
confidence: 95%
“…Carbon dots (CDs) are nanomaterials with a size of less than 10 nm, 1,2 which possess low toxicity, good biocompatibility, and strong light resistance. 3 To precisely regulate the luminescence properties of CDs and develop new applications, various methods have been developed to modulate their physical and chemical properties, [4][5][6] such as doping with heteroatoms, 7 covalent modifications, and non-covalent modifications.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to reinforced connections, they do not require continuity plates, panel zone reinforcement, or strong column-weak beam criteria. Due to the poor performance of pre-Northridge moment connections, researchers began to examine the reasons of failure and create new connections for repair, restoration, and new construction [8]. e current investigation could reduce the failure at beam-column connection.…”
Section: Introductionmentioning
confidence: 99%